ATTRIBUZIONE DI UN IGNOTO SALTERIO DEL XVIII SECOLO Imaging diagnostico sul salterio dipinto appartenente alla collezione di strumenti musicali del Teatro Massimo di Palermo - Alberghina, Francesca; Prestileo, Fernanda; Salerno, Giuseppe; Schiavone, Salvatore (Archeomatica, 2013)
Preliminarily to the restoration of the painted Psalter (most likely attributed to XVIIIth century up until then) coming from the rich collection of musical instruments belonging to the Teatro Massimo in Palermo, a non-invasive optical diagnostics was carried out (diagnostics campaign and restoration by the Centro Regionale per la Progettazione e il Restauro, Assessorato dei Beni Culturali e dell'Identità Siciliana della Regione Siciliana). Diagnostic investigations have involved both the painted scene on the front of the instrument and the wooden structure. Thanks to the results obtained, in particular the analysis in fluorescence induced by ultraviolet radiation, it was possible to uncover, on the back of the Psalter, the manufacturer's autograph inscription showing name, place and year of construction of Psalter, thus making definitive and certain both its attribution and dating. The multispectral imaging has provided interesting information for evaluating the musical instrument state of conservation; to recover the legibility of inscription on its back, the identification of the previous repainting, and the preliminary characterization of some pigments. The radiological imaging, as well as highlighting the fundamental elements to understand the construction technique, allowed us to investigate the state of conservation of the harmonic case affected by two significant fractures.